Repair-defect mutations inhibit rDNA magnification in Drosophila and discriminate between meiotic and premeiotic magnification. - Hawley, R.S.; Marcus, C.H.; Cameron, M.L.; Schwartz, R.L.; Zitron, A.E. (Proceedings of the National Academy of Sciences of the United States of America, 1985)
We have examined rDNA magnification in Drosophila melanogaster males carrying one of 11 recombination- or repair-defective mutations representing seven loci. We show that mutations defined by a defect in postreplication repair (mus-101, mei-41, and mus-108) are also defective in rDNA magnification, whereas mutations that do not affect postreplication repair have little or no effect on magnification. mei-41 inhibits only premeiotic magnification events, while mus-108 blocks both premeiotic and meiotic events. This suggests that meiotic and premeiotic events share some but not all functions. A molecular analysis of rDNA magnification reveals that in mus-108 males, changes in the rDNA restriction pattern can occur within one or a few generations under magnifying conditions. We interpret these data in terms of the role of DNA repair systems in rDNA magnification and in terms of stable maintenance of tandemly repeated genes.